Technology adoption in critical mass games: theory and experimental evidence - Claudia Keser; Irina Suleymanova; Christian Wey (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We analyze the choices between two technologies A and B that both exhibit network effects. We introduce a critical mass game in which coordination on either one of the standards constitutes a Nash equilibrium outcome while coordination on standard B is assumed to be payoff-dominant. We present a heuristic definition of a critical mass and show that the critical mass is inversely related to the mixed strategy equilibrium. We show that the critical mass is closely related to the risk dominance criterion, the global game theory, and the maximin criterion. We present experimental evidence that both the relative degree of payoff dominance and risk dominance explain players' choices. We finally show that users' adoption behavior induces firms to select a relatively unrisky technology which minimizes the problem of coordination failure to the benefit of consumers.
Keywords: C72; C91; D91; D84; 330; Technologiewahl; Netzprodukt; Innovationsdiffusion; Network Externalities; Spieltheorie; Test; Theorie